2013
DOI: 10.1002/tox.21878
|View full text |Cite
|
Sign up to set email alerts
|

Pb2+ induces gastrin gene expression by extracellular signal‐regulated kinases 1/2 and transcription factor activator protein 1 in human gastric carcinoma cells

Abstract: Divalent lead ions (Pb(2+) ) are toxic environmental pollutants known to cause serious health problems in humans and animals. Absorption of Pb(2+) from air, water, and food takes place in the respiratory and digestive tracts. The ways in which absorbed Pb(2+) affects cell physiology are just beginning to be understood at the molecular level. Here, we used reverse transcription PCR and Western blotting to analyze cultures of human gastric carcinoma cells exposed to 10 μM lead nitrate. We found that Pb(2+) induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Pb 2+ activates epidermal growth factor receptor (EGFR) and induces phosphorylation of downstream extracellular signal-regulated kinase (ERK)-1/2, thereby activating AP-1. Overexpression of c-Jun increases activation of the gastrin promoter [ 37 ].…”
Section: Mechanisms Of Heavy Metal Carcinogenicity In the Stomachmentioning
confidence: 99%
“…Pb 2+ activates epidermal growth factor receptor (EGFR) and induces phosphorylation of downstream extracellular signal-regulated kinase (ERK)-1/2, thereby activating AP-1. Overexpression of c-Jun increases activation of the gastrin promoter [ 37 ].…”
Section: Mechanisms Of Heavy Metal Carcinogenicity In the Stomachmentioning
confidence: 99%
“…In this study, half of GI cancers were related to the lower gastrointestinal tracts. The plasma concentrations of Pb in patients with cancer were presented in Table 1 Additionally, the toxic levels of Pb for the gastrointestinal tract dysfunction has been defined in a range of 0.41-0.82 μg/ml (Chan et al, 2015). In this study, the concentration of Pb did not reach the above ranges mentioned earlier.…”
Section: Resultsmentioning
confidence: 61%
“…But, it seems that cancer-prone tissues such as the GI tract have high sensitivity to Pb-induced damage even at lower concentrations. In this context, animal studies demonstrated that exposure to inorganic Pb causes kidney, lung, and brain cancers (Rousseau et al, 2007;Chan et al, 2015;Wynant et al, 2013). Furthermore, the tissue concentration of Pb could be regarded as an issue that needs to be more taken into account.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies report that metals such as chromium, manganese, nickel, arsenic and lead activate Ras/MAPK pathways (Tessier and Pascal, 2006; Andrew et al, 2009; Chan et al, 2015). Cd-induced activation of MAPK and PI3K has also been reported in the ERα-positive cells and this effect is attributed to the xenoestrogenic effect of Cd (Brama et al, 2007; Ponce et al, 2013).…”
Section: Discussionmentioning
confidence: 99%